2021
DOI: 10.1021/acsbiomaterials.1c00663
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled pH-Sensitive Nanoparticles Based on Ganoderma lucidum Polysaccharide–Methotrexate Conjugates for the Co-delivery of Anti-tumor Drugs

Abstract: In tumor therapy, polymer nanoparticles are ideal drug delivery materials because they can mask the disadvantages of anti-tumor drugs such as poor solubility in water, high toxicity, and side effects. However, most polymer-based nanoparticles do not themselves have anti-tumor properties. Herein, a novel pH-sensitive nanoparticle drug delivery system based on Ganoderma lucidum polysaccharides (GLPs), which have demonstrated anti-tumor activities, was designed to enable the delivery of methotrexate (MTX) and 10-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…TG, into the system which resisted further proliferation of the cancer cells hence resulted in lower IC 50 with increasing time. 65 Similarly, the results for HeLa cells showed an efficient anticancer effect of HD-2(TG) nanoparticles where IC 50 values were similar to those for HepG2 cells. Comparative analysis of HD-2(TG) and HD-2 on HeLa and HepG2 cells showed a greater degree of anticancer effect against HepG2 cells as compared with HeLa cells, which might be attributed to higher expression of CD44 receptors on HepG2 cells, as reported in the literature.…”
Section: Mtt Analysissupporting
confidence: 52%
See 1 more Smart Citation
“…TG, into the system which resisted further proliferation of the cancer cells hence resulted in lower IC 50 with increasing time. 65 Similarly, the results for HeLa cells showed an efficient anticancer effect of HD-2(TG) nanoparticles where IC 50 values were similar to those for HepG2 cells. Comparative analysis of HD-2(TG) and HD-2 on HeLa and HepG2 cells showed a greater degree of anticancer effect against HepG2 cells as compared with HeLa cells, which might be attributed to higher expression of CD44 receptors on HepG2 cells, as reported in the literature.…”
Section: Mtt Analysissupporting
confidence: 52%
“…This could be due to sustained release of the entrapped drug, i.e. TG, into the system which resisted further proliferation of the cancer cells hence resulted in lower IC 50 with increasing time 65 . Similarly, the results for HeLa cells showed an efficient anticancer effect of HD‐2(TG) nanoparticles where IC 50 values were similar to those for HepG2 cells.…”
Section: Resultsmentioning
confidence: 81%
“…The NPs are irregularly spherical with uniform particle size, have high drug loading capacity and excellent biocompatibility, and can be rapidly released in the acidic microenvironment of tumor cells. 224 As a natural and renewable biomolecule, dextran is not only biodegradable but also has excellent biocompatibility. 225 Zhao et al constructed HCPT-loaded cinnamaldehyde (CA)-dextran polymers.…”
Section: Organic Npsmentioning
confidence: 99%
“…They can be used as natural drug carrier for nano-drug delivery, which can improve the bioavailability and efficacy of drugs. At present, ASP (Wang et al., 2020 ), bletilla polysaccharide (Wang et al., 2019a ), Ganoderma lucidum polysaccharide (Zheng et al., 2021a ), ursodeoxycholic acid (MDCA) (Anwar et al., 2018 ), Semen Armeniacae Amarum protein (Lin et al., 2020 ) have been successfully used for the delivery of DOX, MTX, sulfasalazine and PTX. A summary of the studies of natural active components as drug carriers in NDCDS is shown in Table 3 .…”
Section: Advantages Of Ndcds Of Natural Drug Active Ingredients and C...mentioning
confidence: 99%